2015
DOI: 10.1155/2015/917670
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Kakkonto, Japanese Traditional (Kampo) Medicine, on Brain Penetration of Oseltamivir Carboxylate in Mice with Reduced Blood-Brain Barrier Function

Abstract: Oseltamivir phosphate (OP) is used to treat influenza virus infections. However, its use may result in central nervous system (CNS) adverse effects. In Japan, OP is used with Kampo formulations to improve clinical effectiveness. We evaluated the potential for using Kampo formulations to reduce CNS adverse effects by quantifying the CNS distribution of oseltamivir and its active metabolite oseltamivir carboxylate (OC) when administered with maoto and kakkonto. We administered lipopolysaccharide (LPS) by intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…It has also been reported that maoto inhibited influenza virus replication in the lungs of mice and exhibited antipyretic effects [13]. Although no direct inhibition of the growth of influenza viruses by kakkonto has been reported, toll-like receptor 4-dependent adjuvant activity of kakkonto [16] and the possibility of kakkonto inhibiting the onset of influenza encephalopathy by acting on the blood-brain barrier [17] have been reported. Jiinkokato and senkyuchachosan have not been reported to be associated with influenza viruses, and this is the first report about the effects of those Kampo drugs on influenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that maoto inhibited influenza virus replication in the lungs of mice and exhibited antipyretic effects [13]. Although no direct inhibition of the growth of influenza viruses by kakkonto has been reported, toll-like receptor 4-dependent adjuvant activity of kakkonto [16] and the possibility of kakkonto inhibiting the onset of influenza encephalopathy by acting on the blood-brain barrier [17] have been reported. Jiinkokato and senkyuchachosan have not been reported to be associated with influenza viruses, and this is the first report about the effects of those Kampo drugs on influenza virus.…”
Section: Discussionmentioning
confidence: 99%
“…Az utóbbi néhány évtizedben a természetes gyógymódokon belül a fitoterápia hatásosságának igazolására Japánban is arra törekszenek, hogy a növényi hatóanyagok és hatásmódok jobb megismerése érdekében komoly kísérletes, analitikai és molekuláris biológiai vizsgálatokban igazolják azok valódi értékét, és feltárják az esetleges mellékhatásokat vagy toxikus tulajdonságokat. Klinikai tanulmányokban igazolják a gyógynövények hasznosságát, létjogosultságát a szintetikus készítmények mellett [13,14]. A kutatások eredményei azonban csak nehezen jutnak el a felhasználókig, ezért célunk, hogy felhívjuk a figyelmet egyes készítmények esetében az óvatosságra.…”
Section: A Kanpó Gyógynövénytudományaunclassified